Mechanical force-induced manipulation of electronic conductance in a spin-crossover complex: a simple approach to molecular electronics. Issue 7 (28th May 2020) - Sarmah, Amrit; Hobza, Pavel
Abstract : The atomic-scale technological sophistication from the last half-decade provides new avenues for the atom-by-atom fabrication of nanostructures with extraordinary precision. Abstract : The atomic-scale technological sophistication from the last half-decade provides new avenues for the atom-by-atom fabrication of nanostructures with extraordinary precision. This urges the appraisal of the fabrication scheme layout for a modular nanoelectronic device based on an individual molecular complex. The mechanical force-induced distortion to the metal coordination sphere triggers a low-spin (LS) to high-spin (HS) electronic transition in the complex. The controlled structural distortions (relative to a specific bond-angle) are deemed to be the switching parameter for the observed spin-transitions. Mechanical stretching is the key to engineering a spin-state switch in the proposed molecular device. The spin-dependent reversible variation in the electronic conductance concurrent to the unique spin-states can be understood from the state-of-the-art Nonequilibrium Green's Function (NEGF) calculations. Combined with NEGF calculations, the DFT study further provides a qualitative perception of the electronic conductance in the two-terminal device architecture. From the transport calculations, there is also evidence of considerable fluctuation in the spin-dependent electronic conductance at the molecular junction with relative variations in the scattering limit. Subsequently, the present study shows significant advances in the transmission probabilities for the high-spin state of the Fe(ii ) complex. The results empower the progress of nanoelectronics at the single molecule level.